Thermodynamic analysis of DNA complexes with methylene blue, ethidium bromide and Hoechst 33258 - Vardevanyan, P.O.; Antonyan, A.P.; Hambardzumyan, L.A.; Shahinyan, M.A.; Karapetian, A.T. (Вiopolymers and Cell, 2013)
Aim. To investigate the thermodynamic characteristics of complexes of calf thymus double-stranded DNA with methylene blue (MB), ethidium bromide (EtBr) and Hoechst 33258 (H33258). Methods. The binding of MB with double-stranded DNA was observed by UV-melting method. Results. Several types of MB binding to DNA-intercalating, semi-intercalating and electrostatic with DNA phosphate backbone, have been revealed at low concentrations of Na+ (2 mM). At high concentrations of cations and low ratios of rb = [ligand]/[DNA] ( 0.05), the molecules of ligand semi-intercalate into the space between adjacent bases. At higher concentrations of ligand the main mode becomes electrostatic binding of MB to DNA phosphate groups. Conclusions. The comparison of thermodynamic characteristics of DNA-MB complexes with those of EtBr and H33258 indicates that there is more than one mode of binding ligands to DNA: besides nonspecific, external electrostatic binding with phosphate groups, intercalation and semi-intercalation modes of interaction coexist. Мета. Дослідити термодинамічні характеристики комплексів дволанцюгової ДНК тимусу теляти з метиленовим синім (МС), бромистим етидієм (БЕ) і Hoechst 33258 (H33258). Методи. Зв’язування МС з дволанцюговою ДНК вивчали методом УФ-плавлення. Результати. Визначено декілька типів зв’язування МС з ДНК: iинтеркаляцiйний, напiвiнтеркаляцiйний і електростатичний з фосфатним остовом ДНК за низьких концентрацій Na+ (2 мМ). За великих концентрацій катіонів і низьких співвідношеннях rb = [ліганд]/[ДНК] ( 0,05) молекули ліганда напівiнтеркалюють у простір між сусідніми основами. За вищих концентрацій ліганда переважаючим способом є електростатичне зв’язування МС з фосфатними групами ДНК. Висновки. Порівняння термодинамічних параметрів комплексів ДНК–МС з такими для БЕ і H33258 виявило більш ніж один спосiб зв’язування лігандів з ДНК. Встановлено, що, окрім неспецифічного, зовнішнього електростатичного зв’язування з фосфатними групами, існують iнтеркаляцiйний і напiвiинтеркаляцiйний типи взаємодії. Цель. Изучить термодинамические характеристики комплексов двухцепочечной ДНК тимуса теленка с метиленовым синим (МС), бромистым этидием (БЭ) и Hoechst 33258 (H33258). Методы. Связывание МС с двухцепочечной ДНК исследовали методом УФ- плавления. Результаты. Обнаружено несколько типов связывания МС с ДНК: интеркаляционный, полуинтеркаляционный и электростатический с фосфатным остовом ДНК при низких концентрациях Na+ (2 мМ). При больших концентрациях катионов и низких соотношениях rb = [лиганд]/[ДНК] ( 0,05) молекулы лиганда полуинтеркалируют в пространство между соседними основаниями. При более высоких концентрациях лиганда основным способом становится электростатическое связывание МС с фосфатными группами ДНК. Выводы. Сравнение термодинамических параметров комплексов ДНК–МС с таковыми для БЭ и H33258 указывает на наличие более чем одного способа связывания лигандов с ДНК. Установлено, что, кроме неспецифического, внешнего электростатического связывания с фосфатными группами, существуют интеркаляционный и полуинтеркаляционный типы взаимодействия.